Pathways to alienation?: a study on the refugee experiences of a group of young Syrian women through the lens of alienation - Nural, Yusuf (2018)
Turkey hosts the world’s largest number of refugees with just over 2.9 million Syrians as of April 2017, out of which nearly half are children and teenagers. Having been provided free access to education, healthcare, lawful residence and protection from involuntary refoulement, family reunification and formal employment, Turkey has undoubtedly been demonstrating a great support for Syrians. Though, the vast majority of Syrians in Turkey are still living in urban, peri-urban and rural areas under poor housing conditions and struggling to generate income and secure their access to welfare benefits. There are still hundreds of thousands Syrian children out of school and only a very small minority of Syrian youth are enrolled in higher education. With these adversities in mind, this study aimed at analysing and gaining an understanding into the lives of a group of Syrian refugee girls and young women in Turkey, from their perspectives, by using the concept of alienation which is mainly represented by social isolation and powerlessness variants. Accordingly, the research questions focused on: what factors prevent them realising their wishes and desires at time of interview and in their futures; and their perceptions as to the changes in their relationships with their peers, family and the surrounding community members after their displacement. Addressing these issues were considered important since the course of the conflict in Syria and Turkey’s reception policies showed that Syrians are not guests anymore, as they were considered at the outset by the Turkish authorities. Therefore, their lack of socioeconomic adaptation in Turkey and social isolation from their acquaintances and social milieu and the majority society would amount to a large number of marginalized and detached group of Syrians in the long term. The empirical data of this study was collected through semi-structured interviews with ten Syrian young women between 17 and 21-years-old. The sample is biased towards females since they have traditionally been secluded in the middle eastern countries including Syria, which motivated this study to reach them. Findings show that, complex interplay of previously established gender norms, male originated safety concerns, and structural and financial deficiencies hamper participants’ power and control over their educational opportunities and freedom of movement and deprives them from meaningful social interactions outside of their domestic spheres. Besides this, their opportunities to have meaningful, supportive, warm and dependable relationships were found to be impaired with loss of or separation from their peers and family members; a lack of Turkish language competency, a lack of quality family time and lastly, weak ties among Syrians. It is contended that, alienation is a useful concept to understand their refugee experiences from a different point of view, yet it is fundamental to revisit it in relation to adolescence, gender, social norms and refugees for future research. Lastly, this study advocates for culturally sensitivity and a holistic approach in social work practice and points out the needs of language training, education and employment opportunities, and safe and accessible social and recreational facilities for Syrian girls and young women in Turkey.